Assessment of Reynolds-averaged Navier-Stokes method for modeling the startup regime of a Darrieus rotor - Ramirez, Jose Miguel (2021)
In this article, the suitability of the Reynolds-averaged Navier-Stokes (RANS) to predict the dynamic response in the startup process of small-scale Darrieus vertical-axis wind turbines (VAWT) was investigated. Using OpenFOAM, numerical simulations have been run to evaluate the regions of the rotor revolution where the prediction of the aerodynamic coefficients is expected to give unreliable results. The qualitative aspects of the prediction of the self-starting of the VAWT for tip speed ratio (λ) ranging from 0 to 3 have been evaluated and to model a more realistic condition, resistive forces acting on the rotor have been implemented. These resistive forces, which are the mechanical friction and the magnetic forces of the generator, were implemented numerically through a viscous damping model and, therefore, a new OpenFOAM library was developed adopting the object-oriented programming methodology as well as the C++ language. From the results, it has been observed that for a λ equal to 0.4 (starting speed), the aerodynamic forces are overestimated for a portion of 82% of the full revolution of the rotor. For a λ equal to 2.70 (steady state), this portion is reduced to 52%. This means that the aerodynamic forces and also the power output are overestimated by a large percentage in a full revolution of the rotor. Therefore, such results allow us to conjecture that RANS modeling may not seem to be an adequate approach to accurately assess the aerodynamic response of VAWTs.